2022
DOI: 10.1186/s12890-022-02055-2
|View full text |Cite
|
Sign up to set email alerts
|

C1QTNF6 regulated by miR‐29a-3p promotes proliferation and migration in stage I lung adenocarcinoma

Abstract: Objective C1QTNF6 has been implicated as an essential component in multiple cellular and molecular preliminary event, including inflammation, glucose metabolism, endothelial cell modulation and carcinogenesis. However, the biological process and potential mechanism of C1QTNF6 in lung adenocarcinoma (LUAD) are indefinite and remain to be elucidated. Therefore, we investigated the interaction among the traits of C1QTNF6 and LUAD pathologic process. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…However, miR-29a-3p expression has been observed in lung adenocarcinoma cells. Studies have found that overexpression of miR-29a-3p is associated with cell proliferation, migration and invasion in LUAD cells [300]. These findings may be related to the observed overexpression of this biomarker in our LUAD-derived exosome samples.…”
Section: Differential Expressed Mirnas In Exosomes Fro M Luad and Luscsupporting
confidence: 53%
“…However, miR-29a-3p expression has been observed in lung adenocarcinoma cells. Studies have found that overexpression of miR-29a-3p is associated with cell proliferation, migration and invasion in LUAD cells [300]. These findings may be related to the observed overexpression of this biomarker in our LUAD-derived exosome samples.…”
Section: Differential Expressed Mirnas In Exosomes Fro M Luad and Luscsupporting
confidence: 53%
“…E2F7 and ANLN, were both involved in the cell cycle process and associated with cell proliferation in malignancy lung cancer [ 67 70 ]. C1QTNF6 had been found to be upregulated in stage I lung cancer tissue and regulated by MIR-29 A-3P to promote proliferation [ 71 ]. What’s more, inhibition of C1QTNF6 could attenuated cell migration, invasion and promoted apoptosis in non-small cell lung cancer [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies related to the cytokine–cytokine receptor interaction pathway have been conducted in many other diseases, as well as pathways that are potentially involved in PCOS. For instance, a study by Lin et al proposed that the miR-29a-3p/C1QTNF6 regulatory axis may promote proliferation and migration in stage I lung adenocarcinoma through the cytokine–cytokine receptor interaction pathway [20] . Another study revealed that SRMS modulates the cytokine–cytokine receptor interaction pathway to regulate colorectal cancer (CRC) progression in colorectal carcinoma patients [21] .…”
Section: Discussionmentioning
confidence: 99%